(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article provides a comparative analysis of phraseological units containing ornithonyms in English and Uzbek languages. Ornithonyms, or bird-related terms, are an important part of phraseology in both languages, reflecting cultural perceptions and conceptualizations of birds. The study examines idiomatic expressions, highlighting the use of ornithonyms in both languages, their meanings, and cultural nuances. The comparison aims to reveal similarities and differences in the usage of bird-related idioms, emphasizing how language and culture are intertwined. This paper also investigates how birds are metaphorically used to describe human traits and behaviors in both linguistic and cultural contexts.